Ответы 2

  • большое спасибо
    • Автор:

      alonzo
    • 5 лет назад
    • 0
  • x^{ -\frac{4}{3} }-2x^{-\frac{2}{3}}-8=0 \\ (x^{ -\frac{2}{3} })^2-2x^{-\frac{2}{3}}-8=0 \\ x^{-\frac{2}{3}}=t \\ t^2-2t-8=0 \\ D=4+4*8=36=6^2 \\ t_1=4;t_2=-2 \\ x^{-\frac{2}{3}} eq -2 \\ x^{-\frac{2}{3}}=4 \\ x^{\frac{2}{3}}= \frac{1}{4}  \\  x^2= \frac{1}{64}   \\ x_1= \frac{1}{8} ;x_2= -\frac{1}{8} ;
    answer img
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years